Possible Threats of the Presence of Non-Native Invasive Land Snail Species in Tiirkiye - Harlioglu, Muzaffer Mustafa; Batool, Zahra; Odabasi, Deniz Anil; Ahmadova, Konul (Kafkas Univ, Veteriner Fakultesi Dergisi, 2024)
Land snails, including some economically important species, are commonly found in forests and mountainous regions of T & uuml;rkiye. T & uuml;rkiye's large geomorphological region and four surrounding seas, which offer a variety of malacofauna, help T & uuml;rkiye achieve an endemism grade of over 65%. Despite extensive research over the past few decades, we still lack a sufficient understanding of the species identification of land snails in T & uuml;rkiye, particularly in areas like forested mountain regions, and it is assumed that there are more than 1000 taxa in total. This review emphasizes the existence of invasive non-native snail species in T & uuml;rkiye, such as Arion ater (Linnaeus, 1758) and Arion vulgaris MoquinTandon, 1855, which have a negative impact on agricultural and horticultural output. In addition to these species, Theba pisana, Cornu aspersum, Xeropicta derbentina, Xeropicta krynickii, Cernuella virgata and Eobania vermiculata are also found in T & uuml;rkiye as nonnative land snail species. Moreover, it also places a strong emphasis on the necessity of managing invasive species to reduce their detrimental effects on natural ecosystems by giving examples from the world and covers the predictions about the possible threats that the presence of non-native invasive land snail species in T & uuml;rkiye may pose in the future.
Keywords: Arion ater; Arion vulgaris; Crop loss; Ecosystems; Environmental problem; Malacofauna